Genomic features of predominant non-PCV13 serotypes responsible for adult invasive pneumococcal disease in Spain. (11th July 2022) - González-Díaz, Aida; Berbel, Dàmaris; Ercibengoa, María; Cercenado, Emilia; Larrosa, Nieves; Quesada, Mª Dolores; Casabella, Antonio; Cubero, Meritxell; Marimón, José María; Domínguez, M Ángeles; Carrera-Salinas, Anna; Càmara, Jordi; et al.
Abstract: Background: Although pneumococcal conjugate vaccines (PCVs) effectively prevent invasive pneumococcal disease (IPD), serotype replacement has occurred. Objectives: We studied the pangenome, antibiotic resistance mechanisms and presence of mobile elements in predominant non-PCV13 serotypes causing adult IPD after PCV13 vaccine introduction in Spain. Methods: We conducted a multicentre study comparing three periods in six Spanish hospitals and analysed through whole genome sequencing representative strains collected in the pre-PCV13, early-PCV13 and late-PCV13 periods. Results: Among 2197 cases of adult IPD identified, 110 pneumococci expressing non-PCV13 capsules were sequenced. Seven predominant serotypes accounted for 42.6% of IPD episodes in the late-PCV13 period: serotypes 8 (14.4%), 12F (7.5%), 9N (5.2%), 11A (4.1%), 22F (3.9%), 24F (3.9%) and 16F (3.6%). All predominant non-PCV13 serotypes were highly clonal, comprising one or two clonal complexes (CC). In general, CC53 8, CC404 8, CC30 16F, CC433 22F and CC66 9N, related to predominant non-PCV13 serotypes, were antibiotic susceptible. CC156 11A was associated with resistance to co-trimoxazole, penicillin and amoxicillin. CC230 24F was non-susceptible to penicillin and resistant to erythromycin, clindamycin, and tetracycline. Six composite transposon structures of the Tn 5252 -family were found in CC230 24F, CC989 12F and CC30 16F carrying different combinations of erm (B), tet (M), and cat . Pangenome analysis revealed differences in accessory genomes among the different CC, with most variety in CC30 16F (23.9%) and more conservation in CC156 11A (8.5%). Conclusions: We identified highly clonal predominant serotypes responsible for IPD in adults. The detection of not only conjugative elements carrying resistance determinants but also clones previously associated with vaccine serotypes (CC156 11A and CC230 24F ) highlights the importance of the accessory genome.